The determinants of fund performance: Does size really matter in South Africa? - Daniel, Ramos (My University, 2018)
Considering the history of maternity leave in South Africa and the traditional position that maternity leave is an exclusive right to women employees only; and recognising the societal changes with regard to parenthood, legislative reform that provides for surrogacy arrangements and same-sex unions, and the limited statutory leave that is available to fathers and parents, other than the birth mother, in terms of s 27 of the Basic Conditions of Employment Act 75 of 1997 (BCEA), the equality provision in the Constitution of the Republic of South Africa Act 108 of 1996 (the Constitution) is examined to consider whether the maternity leave provisions set out in the BCEA unfairly discriminates against fathers, adoptive, surrogacy and same-sex parents on the grounds of gender, sex, sexual orientation and family responsibility. Integral to this, is the groundbreaking judgment of the Labour Court in 2015 in Mia v State Information Technology Agency (Pty) Ltd (2015) 36 ILJ 1905 (LC) in which the court emphasised the importance of the best interest of the child standard in terms of the Children’s Act 38 of 2005, in the consideration of maternity leave. By way of the Labour Laws Amendment Bill 2017, imminent changes to the BCEA is expected to become effective in 2018, which will introduce important changes to the leave provisions by introducing parental leave, adoption leave and commissioning parental leave in relation to surrogacy arrangements. While this is a welcomed and long overdue development, it is argued that these changes are still too limited, and that there remains a need for legislative reform in respect of leave provisions, to provide equal treatment to parents in respect of childcare. It is suggested that South African law makers learn from what the United Kingdom (UK) has adopted in respect of its parental leave provisions, which take cognisance of societal changes and allow parents to share in their leave so that there is equal opportunity for childcare, thereby not placing the duty of childcare only on one parent or one gender as is the case with traditional maternity leave. Apart from this, the UK has introduced extensive paternity leave which is not only applicable to fathers, but also same-sex 6 partners. By looking to the UK, two leave systems are proposed for South Africa, one being shared parental leave and the other a system of ‘maternity leave’ that extends beyond the birth mother and in which fathers or partners are offered parental leave. It is suggested that by introducing these changes to the BCEA, it will limit claims of unfair treatment and discrimination, and will promote the equality provision as is envisaged by the Constitution.
Submitted in partial fulfilment of the requirement for the degree of Masters of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2018